2021
DOI: 10.1038/s41467-021-24168-8
|View full text |Cite
|
Sign up to set email alerts
|

Patient-derived models recapitulate heterogeneity of molecular signatures and drug response in pediatric high-grade glioma

Abstract: Pediatric high-grade glioma (pHGG) is a major contributor to cancer-related death in children. In vitro and in vivo disease models reflecting the intimate connection between developmental context and pathogenesis of pHGG are essential to advance understanding and identify therapeutic vulnerabilities. Here we report establishment of 21 patient-derived pHGG orthotopic xenograft (PDOX) models and eight matched cell lines from diverse groups of pHGG. These models recapitulate histopathology, DNA methylation signat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 75 publications
1
19
0
Order By: Relevance
“…PDOX models are generated by implanting cell suspensions of freshly isolated patient tumor tissues into the comparable tissue of origin in immunodeficient mice. The resultant tumors are closely representative of the original tumor heterogeneity in patients, including the stromal components, architecture, and biochemical interactions (159)(160)(161)(162). Multiple studies have demonstrated that brain tumor PDOX models are transplantable and can be implanted into different brain locations (brain stem, cortex, thalamus, or cerebellum) (161,163).…”
Section: Patient-derived Orthotopic Xenograftsmentioning
confidence: 99%
See 1 more Smart Citation
“…PDOX models are generated by implanting cell suspensions of freshly isolated patient tumor tissues into the comparable tissue of origin in immunodeficient mice. The resultant tumors are closely representative of the original tumor heterogeneity in patients, including the stromal components, architecture, and biochemical interactions (159)(160)(161)(162). Multiple studies have demonstrated that brain tumor PDOX models are transplantable and can be implanted into different brain locations (brain stem, cortex, thalamus, or cerebellum) (161,163).…”
Section: Patient-derived Orthotopic Xenograftsmentioning
confidence: 99%
“…Multiple studies have demonstrated that brain tumor PDOX models are transplantable and can be implanted into different brain locations (brain stem, cortex, thalamus, or cerebellum) ( 161 , 163 ). After multiple passages of PDOX lines in immunocompromised mice, DNA and RNA sequencing of the resultant tumor xenografts revealed that most retain the heterogeneity of their matched patient sample ( 162 ). In addition, comparing surface-antigen profiling of PBT PDOX samples and matched patient samples showed that TAA expression is preserved in these models.…”
Section: Leveraging the Power Of Pbt Models To Improve Car T–cell Efficacymentioning
confidence: 99%
“…The use of low-passage, serum-free, and patient-derived GBM cell cultures has now been widely accepted as the gold standard for in vitro models as they recapitulate specific genetic features and tumor heterogeneity [169]. In fact, the use of patient-derived cell cultures allows the integration of genomic data with drug sensitivity data, which may lead to identification of predictive signatures and enable future stratification of patients to more effective therapy regimens [170]. In particular, patient-derived orthotopic xenograft (PDOX) models have been proposed as a model for testing therapeutics aimed at preventing GBM recurrence as they allow the recreation of the genetic, histologic, and morphologic profiles of human GBM [171,172].…”
Section: In Vitro Models For Drug Resistancementioning
confidence: 99%
“…Similarly, investigation into the RNA polymerase II (RNAPII) transcriptional machinery has gained traction in recent years [ 18 , 73 ]. This includes targeting CDK7 in order to prevent RNAPII phosphorylation and subsequent transcription initiation, with the CDK7 inhibitor THZ1 having been shown to suppress tumour growth in orthotopic DMG orthotopic [ 74 ]. More recently, CDK9 suppression has demonstrated anti-tumour effects in DMG models [ 75 ].…”
Section: Targeting Epigenetic Mechanisms In Dmgsmentioning
confidence: 99%